Optimization of Soy‐Butter from Sprouted Soybean and its Quality Parameters. Issue 1 (15th January 2014) - Murugkar, Dipika Agrahar; Kotwaliwale, Nachiket; Gupta, Chetan; Gulati, Paridhi; Kumar, Manoj
Abstract The time and temperature of roasting of sprouted soybean was optimized using response surface method. The effect of roasting on sprouted whole kernel of soybean indicated that roasting time and temperature individually, as well as in combination, had a significant effect on hardness of roasted kernels. Sprouted soybean kernels were roasted at optimized temperature (127C) and time (37 min) and subsequently made into soy‐butter (SB) and compared with reference soy‐butter (RSB) on the basis of nutrient content, particle size, color, sensory quality and rheology. SB contained 38 g/100 g protein and 34 g/100 g fat. There was significant difference (P < 0.05) between RSB and SB in L* values. Sprouting improved flavor scores and SB showed higher organoleptic acceptability compared with RSB on a 9‐point hedonic scale. Rheology showed that SB behaved like viscoelastic shear thinning material; like Bingham plastic at lower shear rates and Herschel‐Bulkley (HB) fluid at higher shear rates. Practical Applications Soybean is an important crop due to its high protein content but soy products are not very popular due to problems of trypsin inhibitor, off‐flavors, etc. Sprouting is a process known to improve the nutritional and functional quality while reducing the content of trypsin inhibitors and off‐flavors of the bean and consequently of the product. SB, a comparatively new product of soybean, offers all positive attributes of soybeans, sprouting and sensory qualities of vegetable butters. A new process for manufacture of SB has been proposed in this paper. The nutrient quality, particle size and rheology have been studied. The process is simple and does not require any expensive or specialized equipment for commercial manufacture. Quality attributes of the product have been modeled so that effect of any change in process on the quality of product can be predicted or the manufacture process can be modified to achieve certain quality attribute.